The novel GlcNAc 6-phosphate dehydratase NagS governs a metabolic checkpoint that controls nutrient signaling in Streptomyces - Li, Chao; Urem, Mia; Kotsogianni, Ioli; Lau, Josephine; Du, Chao; Elsayed, Somayah S.; Martin, Nathaniel I.; McNae, Iain W.; Voskamp, Patrick; Mayer, Christoph; Rigali, Sébastien; Pannu, Navraj; et al. (PLOS Biology, 2025)
Streptomyces bacteria are renowned for their multicellular lifestyle and as Nature’s medicine makers, producing the majority of the clinical antibiotics. A landmark event during early development is the lytic dismantling of the substrate mycelium. Degradation of the hyphal cell-wall leads to the accumulation of N-acetylglucosamine (GlcNAc) in the colonies, which is a metabolic checkpoint during the onset of development and antibiotic production. Here, we show that GlcNAc sensing requires a toxicity pathway dependent on the enzyme GlcNAc-6P dehydratase (NagS). Dehydration of GlcNAc-6P by NagS to 6P-chromogen I is an unprecedented reaction in central metabolism that is highly conserved in – and limited to – the Streptomycetaceae. 6P-chromogen I is metabolized into a structural analogue of ribose by a promiscuous activity of GlcNAc-6P deacetylase NagA. Toxicity is relieved by supplementing the growth media with ribose. Structure-function analysis of NagS not only highlighted key residues in the active site of the enzyme in interaction with its substrate GlcNAc-6P, but also revealed 6-phosphogluconate as its catalytic inhibitor. Our work uncovers a conserved metabolic toxicity pathway in Streptomyces that revolves around a novel enzyme that plays a key role in nutrient signaling.